2014
DOI: 10.1039/c4fo00118d
|View full text |Cite
|
Sign up to set email alerts
|

Transamidation of gluten proteins during the bread-making process of wheat flour to produce breads with less immunoreactive gluten

Abstract: Due to an increasing incidence of celiac disease (CD) and other gluten-related disorders, different gluten-free breads have been developed using starches and additives as a substitute for gluten. Thus, patients miss not only the taste and aroma of wheat bread but also risk their sensitive intestines. Therefore, modifying gluten to avoid an immune response in CD and its application to baking is in progress. The aim of the study was to enzymatically modify gluten on wheat flour, during bread-making avoiding the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…14 It was found that the reactivity between gluten proteins and R5 mAb was reduced by 42% using R5 ELISA when gluten proteins were modied by mTG and lysine. 15 Moreover, previous studies show that the transamidation by mTG/tTG with appropriate acyl-acceptor substrates (lysine or lysine methyl ester) can be used to prevent the immunological activity of gluten proteins, while as it was not sufficient in abolishing the gluten activity. [16][17][18][19] In addition, recent study highlighted the potential of mTG transamidation to block nonimmune mechanisms related to gluten toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…14 It was found that the reactivity between gluten proteins and R5 mAb was reduced by 42% using R5 ELISA when gluten proteins were modied by mTG and lysine. 15 Moreover, previous studies show that the transamidation by mTG/tTG with appropriate acyl-acceptor substrates (lysine or lysine methyl ester) can be used to prevent the immunological activity of gluten proteins, while as it was not sufficient in abolishing the gluten activity. [16][17][18][19] In addition, recent study highlighted the potential of mTG transamidation to block nonimmune mechanisms related to gluten toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Although only associative, epidemiological survey showed a correlation between the increased CD incidence and the continuous surge in consumption of enzymes in the bakery industries, mTG being a major one [6,14]. Finally, wheat or gluten containing products enzymatically treated by mTG were shown to be immunogenic, inducing antibodies when consumed by humans [56][57][58][59][60][61][62][63][64][65], thus substantiating the serological studies on mTG immunogenicity [13,27].…”
Section: Additional Observations Related To Potential Mtg Pathogenicimentioning
confidence: 63%
“…Olivier et al (2012) found that inducing polymerization of blactoglobulin using MTGs decreased in vivo allergenicity but did not decrease in vitro humoral or ex vivo cell-mediated immunoreactivity. Also treatment of gluten with MTG reduced its allergenicity (Clare and Daubert 2011;Erickson et al 2012;Heredia-Sandoval et al 2014). On the other hand, novel probiotic delivery system that efficiently releases Lactobacillus bulgaricus into the lower intestines was developed using MTG cross-linked soy protein incorporated with agro-wastes (Yew et al 2011) demonstrating the scope of applications of these enzymes.…”
Section: Unconventional Applications Of Microbial Transglutaminases (mentioning
confidence: 98%
“…Nowadays, with the challenges of sustainability and developing functional novel foods and products, microbial transglutaminases have been used in the development of entirely new products such as edible protein films used for food protection (Di Pierro et al 2013). MTGs are more frequently used as protein modifiers to improve nutritional value of specific proteins or to lower allergenic potential (Giosafatto et al 2012;Han et al 2013;Heredia-Sandoval et al 2014). Olivier et al (2012) found that inducing polymerization of blactoglobulin using MTGs decreased in vivo allergenicity but did not decrease in vitro humoral or ex vivo cell-mediated immunoreactivity.…”
Section: Unconventional Applications Of Microbial Transglutaminases (mentioning
confidence: 99%